Diversidade religiosa e formação de professores de ciências: uma discussão em Habermas e um caso no ensino de Física - Azevedo, Hernani Luiz; Camargo, Eder Pires de [UNESP] (My University, 2013)
This article brings a discussion of the implications of religious diversity on science education as well as on teacher education. To orientate our discussion, we adopt as framework the ideas of German philosopher Jürgen Habermas on the political relationship that should govern relations between a naturalistic culture and different religious cultures. We also present a research with future teachers of physics, which aimed at investigating the positions taken by the future teachers towards non scientific models presented by students about the origins of the universe. We tried to identify, especially, the expectation of these future teachers would demonstrated about the contributing of the lifting of such models in class by students. We were able to find that most of them believe that the manifestation of these ideas could bring contributions to the discussion in the classroom. We also found that teaching practices based on communication, questioning and dialogue of the undergraduate course done by the prospective teachers has generated an ownership by the undergraduates of these practices and their potential application in other situations and other discussions, including inter-religious.

Neste artigo, propomos uma discussão sobre as implicações da diversidade religiosa no ensino de ciências, bem como sobre a formação de professores de ciências. Baseamo-nos, para tanto, nas reflexões do filósofo alemão Jürgen Habermas sobre o relacionamento político que deve regular as relações entre uma cultura secularizada e as diversas culturas religiosas. Também apresentamos uma pesquisa feita com futuros professores de Física, na qual investigamos as posturas adotadas por estes futuros profissionais diante de modelos não científicos (religiosos) apresentados por alunos sobre as origens do Universo. Buscou-se identificar, principalmente, a expectativa que tais futuros professores demonstravam quanto à contribuição (ou não) do levantamento de tais modelos durante a aula por parte dos alunos. Tivemos a oportunidade de constatar que a maioria deles acredita que a manifestação dessas concepções poderia trazer contribuições para a discussão em sala de aula. Também verificamos que práticas pedagógicas baseadas na comunicação, no questionamento e no diálogo, em disciplinas do curso de licenciatura concluído pelos futuros professores, têm gerado uma apropriação destas práticas por parte dos licenciandos, e sua potencial aplicação em outras situações e discussões, inclusive interreligiosas.
Religious diversity and teacher education: a discussion based in Habermas’s views and a case at physics teaching
Keywords: Religious diversity; Science education; Teacher education; Communicative competence; Diversidade religiosa; Ensino de ciências; Formação de professores; Competência comunicativa